2003
DOI: 10.1097/01.ju.0000096421.56225.79
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Intrarenal Lithotripsy Outcome After Failure of Shock Wave Lithotripsy

Abstract: RIRL effectively and safely alleviated upper tract stones unresponsive to earlier SWL. It can be considered salvage therapy in such cases. RIRL is well suited for treating stones less than 2 cm with better stone-free rates than SWL in the same circumstances. Residual stones were more likely in lower pole cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 18 publications
4
29
1
1
Order By: Relevance
“…The other patient with a single kidney developed obstructive anuria 1 month after the last procedure due to earlier disintegrated fragments and was managed successfully with ureteroscopy and a DJ stent. The overall complication rate (20.7%), which is reported in our study, is comparable to similar published series [11,12,[20][21][22][23].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The other patient with a single kidney developed obstructive anuria 1 month after the last procedure due to earlier disintegrated fragments and was managed successfully with ureteroscopy and a DJ stent. The overall complication rate (20.7%), which is reported in our study, is comparable to similar published series [11,12,[20][21][22][23].…”
Section: Discussionsupporting
confidence: 94%
“…The overall complication rate of ureteroscopy, which is reported in recent literature lies between 6 and 23% [9,11,12,[17][18][19][20][21][22][23][24]. In our study, the overall complication rate was 20.7%.…”
Section: Discussioncontrasting
confidence: 38%
“…Stav et al [51] reported a SFR of 67% in 81 patients with a history of unsuccessful SWL. Holland et al [52] compared 93 patients, whom were divided into two groups of 42 patients with primary treatment and 51 patients with secondary treatment (92% after SWL, 8% after PCNL).…”
Section: Rirs As a Second-line Therapymentioning
confidence: 99%
“…[20] ESWL başarısızlığı sonrası böbrek taşlarında retrograd intrarenal cerrahi uygulamasının yüksek başarı ve ESWL'den daha iyi taşsızlık oranlarına sahip olduğu da bilinmektedir. [21,22] Çalışmamızda ESWL sonrası ÜRS yapılan hastalarda başarı oranı ESWL öyküsü olmayanlardan anlamlı derecede düşük bulundu. ESWL öyküsünün artmış reoperasyon, double J stent ve/veya üreteral stent gereksinimi ile ilişkili olmadığı ancak ek alet kullanımını %56 oranında arttırdığı tespit edildi.…”
Section: Discussionunclassified